Wine Aromas (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Wine has a complex matrix with many volatile compounds present, which evolves over time. These volatile compounds are important to wine quality as they contribute to the aroma and varietal characteristics of wine. Recent development in the analysis of volatile compounds in wine has greatly improved our understanding of the complexity of wine aroma. Analytical methods used for wine aroma fingerprinting have shown potential in determining the origin and quality of wine. Thus, research on volatile compounds responsible for wine aroma and their correlation with wine provenance and wine quality have increasingly attracted great interest from researchers and winegrowers. This Special Issue presents the latest research regarding wine aroma compounds, including, but not limited to, the topics on the characterization of aroma compounds in grapes and wine, factors influencing the production of aroma compounds in wine during fermentation and maturation, and analytical methods for wine aroma analysis.